Time‐Dependent Consolidation in Porous Geomaterials at In Situ Conditions of Temperature and Pressure. Issue 8 (16th August 2018) - Choens, R. C.; Chester, F. M.
Abstract: Analysis of quartz sandstones shows that grain‐scale crushing (fracture and rearrangement) and associated sealing of fractures contribute significantly to consolidation. The crushing strength ( P* ) for granular material is defined by laboratory experiments conducted at strain rates of 10 −4 to 10 −5  s −1 and room temperature. Based on experiments, many sandstones would require burial depths in excess of the actual maximum burial depth to create observed microstructure and density. We use experiments and soil mechanics principles to determine rate laws for brittle consolidation of fine‐grained quartz sand to better estimate in situ failure conditions of porous geomaterials. Experiments were conducted on St. Peter sand utilizing different isostatic consolidation and creep load paths at temperatures to 200 °C and at strain rates of 10 −4 to 10 −10  s −1 . Experiment results are consistent with observed rate dependence of consolidation in soils, and P* for sand can be identified by the change in the dependence of consolidation rate with stress, allowing the extrapolation of P* determined in the laboratory to geologic rates and temperatures. Additionally, normalized P* values can be described by a polynomial function to quantify temperature, stress, and strain‐rate relationships for the consolidation of porous geomaterials by subcritical cracking. At geologic loading rates, P* for fine‐grained quartz sand is achieved within ~3‐km burial depth, and thus, shear‐enhanced compaction under nonisostatic stress can occur at even shallower depths. These results demonstrate that time and temperature effects must be considered for predicting the brittle consolidation of sediments in depositional basins, petroleum reservoirs, and engineering applications. Key Points: Isostatic consolidation and creep experiments were performed on water‐saturated quartz sand at elevated temperatures and slow strain rates Consolidation behavior of quartz sand by subcritical cracking is similar to temperature and strain rate dependencies of clay‐rich soils The conditions in situ for grain crushing during burial of quartz sand can occur within 3‐km depth, consistent with natural observations